2023
DOI: 10.1038/s41598-023-33023-3
|View full text |Cite
|
Sign up to set email alerts
|

An updated meta-analysis of effects of curcumin on metabolic dysfunction-associated fatty liver disease based on available evidence from Iran and Thailand

Abstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a common cause of chronic liver disease and can progress to nonalcoholic steatohepatitis and cirrhosis. This study aims to summarize the evidence for the effects of curcumin on MAFLD progression. Studies were identified from Medline and Scopus databases until April 2022. Systematic reviews and meta-analyses (SRMA) and randomized controlled trials (RCT) were selected based on pre-specified criteria. Three reviewers independently extracted data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The effects of turmeric and different forms of curcumin on blood glucose concentrations were assessed from meta-analyses in which subjects exhibited diverse disorders such as MetS, NAFLD, PCOS, T2DM, and CVD 32,49–68 . Compared with controls, most meta-analyses showed a consistent, statistically significant effect of curcumin in decreasing FBG levels (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of turmeric and different forms of curcumin on blood glucose concentrations were assessed from meta-analyses in which subjects exhibited diverse disorders such as MetS, NAFLD, PCOS, T2DM, and CVD 32,49–68 . Compared with controls, most meta-analyses showed a consistent, statistically significant effect of curcumin in decreasing FBG levels (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Histological findings from rodent studies showed that curcumin and related substances ameliorated liver fibrosis by inhibiting hepatic stellate cell proliferation, collagen synthesis, and matrix metalloproteinase and reduced the number of necrotic cells in a dose-dependent fashion [254]. In a recent meta-analysis of Asian clinical trials conducted for 8-12 weeks involving supplementation with different forms of curcumin, small but significant reductions in AST and ALT levels (but not in cholestasis markers) were observed, together with a significant reduction in ultrasound-evaluated liver steatosis, BMI, waist circumference, fasting blood glucose and total cholesterol; no significant variation in liver fibrosis at transient elastography was demonstrated, but this parameter was evaluated only in two studies [255]. Recent murine data suggest a possible muscle-specific response to curcumin treatment, with prevention of muscle mass loss, reduction of age-related muscle force loss and overall reduction in mortality in old mice [256,257].…”
Section: Carnitinementioning
confidence: 99%
“…In a meta-analysis of 16 randomized clinical trials conducted by Ngu et al, including 1028 patients with MAFLD, the effect of curcumin supplementation on various metabolic parameters was assessed. Curcumin was shown to reduce the severity of MAFLD (RR = 3.52; 95% CI: 1.27-9.72) and increase liver steatosis resolution (RR = 3.96; 95% CI: 1.54-10.17 ], an increase in the resolution of hepatic steatosis (as measured using ultrasonography) (MD = 3.53; 95% CI: 2.01-6.22), and a reduced fasting blood sugar, body-mass index, and total cholesterol concentration [218].…”
Section: Functional Foods 101 Curcuminmentioning
confidence: 99%